NINJA FUTURE : SECRETS TO SUCCESS IN THE NEW WORLD OF INNOVATION - Shapiro, Gary
Summary: In Ninja Future, Shapiro explains the evolving technological landscape, breakthroughs underway now and those we can only envision. New innovations such as self-driving vehicles, blockchain, 5G, the Internet of Things, and countless others will